« Screens, screens, it’s nothing but screens! » La profusion des écrans à l’Exposition Universelle de Shanghai, 2010 - Tatjana Barazon; Van Troi Tran (Conserveries Mémorielles)
This article uses the example of visual devices at the Shanghai World Expo in 2010 in order to develop a reflection on the place of screens in both the fabric of artificial environments, a phenomenon characteristic of world’s fairs since the 19th Century, and the diffraction of the visitor’s experience by the proliferation and the democratization of screens. Whereas world’s fairs appear to embody consensual grand narratives of progress, a close examination of the social life of the animated images that people their ecologies uncover an event that is also rich in openings, multiplicities and virtualities.